2004
DOI: 10.1159/000075306
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-Activating Factor Concentration in the Stool of Human Newborns: Effects of Enteral Feeding and Neonatal Necrotizing Enterocolitis

Abstract: Epidemiologic studies have identified enteral feedings as a risk factor for necrotizing enterocolitis (NEC). Enteral feedings provide the substrate for colonization of the newborn gut with gram-negative bacteria with endotoxin production, which may trigger the production of endogenous inflammatory mediators, including platelet-activating factor (PAF). In this prospective study, we examined the effect of enteral feeding on PAF concentration in the stool of preterm and full-term human newborns. The concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
4

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 25 publications
0
18
0
4
Order By: Relevance
“…Therefore, the absence of a consistent, reliable, and early marker of intestinal inflammation in the peripheral blood has been one of the great challenges for the diagnosis and management of NEC [7,26]. Although some serum markers such as CRP, interleukin-6, and platelet-activating factor have been studied, all of them showed a lack of specificity [9,27,28]. There are also conflicting data about the use of these inflammatory mediators in the diagnosis and follow-up of NEC [8][9][10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the absence of a consistent, reliable, and early marker of intestinal inflammation in the peripheral blood has been one of the great challenges for the diagnosis and management of NEC [7,26]. Although some serum markers such as CRP, interleukin-6, and platelet-activating factor have been studied, all of them showed a lack of specificity [9,27,28]. There are also conflicting data about the use of these inflammatory mediators in the diagnosis and follow-up of NEC [8][9][10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…Seven of the infants subsequently developed NEC. The mean stool PAF level in the infants with NEC was approximately 3 to 4 times higher than levels seen in the stools from healthy infants at similar ages [28]. Ewer et al [29] have shown in a neonatal pig model that the administration of the PAF antagonist WEB2170 ameliorates vascular responses after hypoxiaendotoxin challenge, suggesting that this animal model may be useful in evaluating preventative or therapeutic interventions for infants.…”
Section: Feeding and Inflammatory Mediatorsmentioning
confidence: 96%
“…The initiation of enteral feeding results in a surge of plasma PAF in preterm infants [27]. Amer et al [28] measured PAF content in stools of 68 preterm infants before and after the initiation of feeding. Seven of the infants subsequently developed NEC.…”
Section: Feeding and Inflammatory Mediatorsmentioning
confidence: 99%
“…Elevated stool PAF concentrations were detected (1) when enteral nutrition was initiated in preterm neonates, and (2) in patients with NEC [108,109].…”
Section: Platelet-activating Factormentioning
confidence: 99%